If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -9 = 3x + -21 Reorder the terms: -9 + 5x = 3x + -21 Reorder the terms: -9 + 5x = -21 + 3x Solving -9 + 5x = -21 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -9 + 5x + -3x = -21 + 3x + -3x Combine like terms: 5x + -3x = 2x -9 + 2x = -21 + 3x + -3x Combine like terms: 3x + -3x = 0 -9 + 2x = -21 + 0 -9 + 2x = -21 Add '9' to each side of the equation. -9 + 9 + 2x = -21 + 9 Combine like terms: -9 + 9 = 0 0 + 2x = -21 + 9 2x = -21 + 9 Combine like terms: -21 + 9 = -12 2x = -12 Divide each side by '2'. x = -6 Simplifying x = -6
| -30-b=15 | | 9x-9=3x-21 | | 3x(4k-8)+x(k-2k)+2k+27=0 | | -30-b=-15 | | 4(x-5)=5x-25 | | -21-c=10 | | -9b=8 | | -123=-23-20y | | 103=30x+13 | | 24+11y=112 | | 61-2x=7-6x | | 1.8q-10.1q+1.3=-65.1 | | -2*sin(x)-2*cos(x)=0 | | -2sin(x)-2cos(x)=0 | | -6x+7+7x-3=-5x+6x+7 | | x+1.6=9.5 | | 3c-2b-(3b-c)= | | -x^2-4x-13=0 | | -3x+4=4-3x | | 4a+4b-5c= | | -7x^2-91x-294=0 | | 3x+49=94 | | 1.46e+299=0 | | 1.46e-6=0 | | 5*5-2=23 | | 5*5/8 | | 8-x=4-5(2+x) | | 8x^3+9x^2-6x-7=0 | | 0.092(0.94)= | | 8-(1/6)x^2-(1/3)x=0 | | 6/7x-2/7=5 | | Cos(6x)+3cos(3x)=1 |